Pension Reforms and Austerity effects in Portugal (2007-2017) - Carolo, D. (11h ESPAnet ITALY Conference, 2018)
The objective of this paper is to examine whether the austerity measures taken in Portugal between 2010-2014, followed by a period of “policy reversals” promoted by the new Government after 2015, have led to institutional change in the core of welfare regime, particularly on the pension system. Prior to the financial crisis Portugal was already a case study. When the main features of Ferrera’s Southern European Welfare regime were applied to Portugal (Adão e Silva 2002), there was evidence of remarkable institutional change: to tackle the poverty issue were created new programs such as the minimum income (RMG -1998) and the complementary subsidy for elderly (CSI - 2005), while pensions schemes were reformed several times 2000, 2002, and 2007 in order to ensure better sustainability. The result minimized some of its regressive features and improved redistribution equity, which seems to be easier when in line with a cost-containment purpose (Carolo, 2015). Regarding the pension system the 2007 Reform in Portugal was even praised at the EU level, seen as good example of compromise between social guarantees and addressing expenditure risks in the long term. This was due to the introduction of a sustainability factor instead of an retirement age increase (Carolo, 2010). This convergence, similar to other Southern European countries, at that time, could be seen as “Starting from periphery, becoming centre” (Guillén, 2007). The crisis hit in 2008/2009 and Portugal implemented the ‘TROIKA’ recommendations (2011- 2014). Public cost containment became the major priority and welfare reform was again at stake. But institutional reality contrasts sharply with Greece, for example (see Angelaki 2016), due to the reforms already implemented or under way. As a result, taxes increased and most social benefits were reduced but there was no evidence of structural change at the institutional level. Until today there is only one study providing evidence about income inequality variation during this period (Rodrigues et al, 2016). Although at the political level there are several questions yet to be addressed:  If the pension reform was already implemented before Crisis (2007), how to justify further cuts at the policy level? Abstract ￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼￼1  If the Government that implemented austerity didn’t lose elections, can it be argued that most of the people disagreed on the austerity policies?  The new Government known as “Geringonça” (Socialist party with support of communist party and radical left) promised a new economic policy based on cuts reversion/income devolution to increase consumption, which have been followed. Nevertheless, austerity was not displaced (sustainability factor remains distorted; social benefits reductions still in place) and Government popularity continues to rise (Expresso Pool, 16/03/2018). In order to provide some evidence to answer those questions this analysis follows the political economy approach and redistribution analysis of pension systems (Lindert, 2004). Thus, all the measures taken in this period regarding pension and social benefits entitlements, which includes labour market social protection, will be analysed in terms of public expenditure and redistribution effects. This analysis brings some empirical evidence about one of the identified features of the Southern European model identified by Ferrera (1996). For the first time ever the left parties (PCP and BE), previously represented in Parliament as protest parties are now supporting a Government. Thus, the analysis of expenditure and redistribution effects will also provide the opportunity to compare austerity measures recommended by TROIKA and implemented by right wing-conservative coalition Government (PSD-CDS) with policy reversals decided by the Socialist Government (PS) with support of all left parties. By focusing this paper specifically on Portugal it aims to provide some evidence across the variation among Southern European countries.